Progiraffa (Artiodactyla: Ruminantia: Giraffidae) from the Lower Siwalik Subgroup (Miocene) of Pakistan. Issue 2 (2nd April 2016) - Aftab, Kiran; Khan, Muhammad Akbar; Ahmad, Zaheer; Akhtar, Muhammad
Abstract : Aftab, K., Khan, M.A., Ahmad, Z. & Akhtar, M., February 2016. Progiraffa (Artiodactyla: Ruminantia: Giraffidae) from the Lower Siwalik Subgroup (Miocene) of Pakistan. Alcheringa 40, xxx–xxx. ISSN 0311-5518 Previously, Progiraffa exigua has been reported only from the Kamlial Formation ( ca 18.3–14.2 Ma) of the Siwalik Group. We record Progiraffa exigua from the Lower Siwalik Subgroup at five localities: Jaba, Chinji Rest House, Rakh Wasnal, Dhok Bun Amir Khatoon and Ghungrila, Pakistan, thus extending the range of P. exigua to the Chinji Formation of the Siwalik Group ( ca 14.2–11.2 Ma). Kiran Aftab [ kiranaftab2012@gmail.com ], Zaheer Ahmad [ dr.zaheerahmed11@yahoo.com ], Zoology Department, GC University, Lahore, Pakistan; Muhammad Akbar Khan [ akbaar111@yahoo.ca ], Muhammad Akhtar [ drakhtarfdrc@hotmail.com ], Dr Abu Bakr Fossil Display & Research Centre, Zoology Department, University of the Punjab, Lahore, Punjab, Pakistan.